The Right of First Offer in European Law - Vlad Ionut Savu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2022)
The present study aims to offer an integrated vision on the origin, legal nature and the effects which occur in the field of specific relations of civil law, from the perspective of comparative law by valorizing the specific research methods which define the institution of the right of first offer. Theoretical approaches with practical implications of continental law and Anglo-Saxon law were considered.